IMPLEMENTASI KURIKULUM PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH MENENGAH ATAS AL-AZHAR MEDAN - Derliani Daulay (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2019)
This study aims to describe the learning implementation of Islamicreligious education curriculum in improving the quality of education inAl-Azhar High School Medan. Include; Curriculum design, efforts toimprove the quality of education, planning, implementation, andevaluation. Data collection techniques using observation, interviews. Dataanalysis techniques using data reduction, data display, and conclusiondrawing / verification. The results of the study show that: 1) The design ofthe Islamic religious education curriculum that is used in Al-Azhar MedanHigh School is the same as the government curriculum, only there isdevelopment in the material. 2). Efforts are made in improving the qualityof education by taking into account the education, output and process ofeducation. 3) Implementation of the PAI curriculum in the presence of:planning, implementing, and evaluating education.